The Invisible Students: Service Excellence in the Second Year. Issue 183 (13th August 2018) - Nelson, Denise D.
Abstract: This chapter examines areas in which institutions may be falling short of satisfying sophomores' expectations for the everyday interactions of life on campus. It provides recommendations for demonstrating institutional values in practical ways that express care for sophomores and interest in meeting their needs effectively.